Legal Protection for Medical Volunteers in the Implementation of Emergency Medical Measures - Pont, Anna Veronica (Poltekkes Kemenkes Palu, 2023)
The presence of medical volunteers during a medical emergency is very much needed and expected. Their presence is temporary according to the duration of the crisis. However, the current regulations do not explicitly discuss legal protection for medical volunteers during a health emergency. This type of research is normative juridical research that focuses on examining the application of rules or norms in positive law, especially concerning legal synchronization. Due to the type of normative juridical research, the approach used is the statute approach, which is taken by examining various laws that have to do with the legal issues being handled. The results of the study explain that the form of legal protection for medical volunteers in an emergency period can be understood and developed in the context of health, disaster, and employment regulations, namely Law Number 36 the Year 2009 concerning Health, Law Number 29 the Year 2004 concerning Medical Practice, Law No. 36 of 2014 concerning Health Workers and Law Number 38 of 2014 concerning Nursing, Regulation of the Minister of Health of the Republic of Indonesia Number 75 of 2019 concerning Health Crisis Management, Law Number 11 of 2020 concerning Job Creation. For its implementation, several Decrees of the Minister of Health and Circular Letters of the Ministry of Manpower were issued which regulate and guarantee legal protection for health workers, including medical volunteers, during a health emergency which includes protection of work norms, protection of Occupational Health and Safety norms and protection labor social security norms.